2009
DOI: 10.1017/s1138741600002018
|View full text |Cite
|
Sign up to set email alerts
|

Public Responses to Intimate Partner Violence Against Women: The Influence of Perceived Severity and Personal Responsibility

Abstract: This paper explored public willingness to act when exposed to cases of intimate partner violence against women, by analyzing the influence of perceived severity and personal responsibility on two types of responses: mediating and reporting to the police. Results (N = 419) yielded main effects of personal responsibility for both types of responses. No main effects of perceived severity were found. A significant interaction between perceived severity and personal responsibility was found only for reporting respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
93
1
15

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(125 citation statements)
references
References 41 publications
5
93
1
15
Order By: Relevance
“…Results from socio-demographic variables analyses showed that women report a more positive attitude toward reporting partner violence than men. This finding is in line with research suggesting that women perceived partner violence as more severe, are less accepting, and feel more personal responsible to act than men, which suggest greater empathy for the victims [4,66,67]. None of the other sociodemographic controls explores yielded significant differences.…”
Section: Discussionsupporting
confidence: 88%
“…Results from socio-demographic variables analyses showed that women report a more positive attitude toward reporting partner violence than men. This finding is in line with research suggesting that women perceived partner violence as more severe, are less accepting, and feel more personal responsible to act than men, which suggest greater empathy for the victims [4,66,67]. None of the other sociodemographic controls explores yielded significant differences.…”
Section: Discussionsupporting
confidence: 88%
“…Dicha cuestión debería ser clarificada en estudios posteriores. Sin duda, resulta de gran importancia en este ámbito la actitud de tolerancia o intolerancia hacia la violencia doméstica contra la mujer (Gracia y Herrero, 2006b;Gracia, García y Lila, 2009;Lila, Gracia y García, 2010), sin embargo, según muestran los resultados, no parece relacionarse con el consumo de alcohol.…”
Section: Discussionunclassified
“…This instrument presents eight IPVAW situations (e.g., "During an argument, a man hits his partner and afterwards he asks for her forgiveness") to which respondents had to rate the severity of each situation (ranging from 1, not severe at all, to 10, extremely severe). This instrument was validated in the general Spanish population, and with police officers and intimate partner violence offenders, showing acceptable psychometric properties, and has been related to IPVAW victim blaming attitudes, personal responsibility, sexism, and empathy (Gracia et al, 2009;Gracia & Tomás, 2014;Vargas, Lila, & Catalá-Miñana, 2015). The scale showed a good internal consistency in the recruited general sample (Cronbach's α = .89).…”
Section: Instrumentsmentioning
confidence: 99%
“…Perceived severity of IPVAW (PS-IPVAW; Gracia, García, & Lila, 2008, 2011. This instrument presents eight IPVAW situations (e.g., "During an argument, a man hits his partner and afterwards he asks for her forgiveness") to which respondents had to rate the severity of each situation (ranging from 1, not severe at all, to 10, extremely severe).…”
Section: Instrumentsmentioning
confidence: 99%